Potential Natural Blend Hydrosol TGLON Suppresses the Proliferation of Five Cancer Cell Lines and Also Ameliorates Idiopathic Pulmonary Fibrosis in a Mouse Model - Wei-Hsiang Huang; Mei-Lin Chang; Ching-Che Lin; Chih-Peng Wang; Feng-Jie Tsai; Chih-Chien Lin (Pharmaceuticals)
Background: Cancer and fibrotic diseases represent major global health challenges, underscoring the need for safe, multifunctional natural therapies. Although natural products possess notable anticancer properties, their clinical translation is often hindered by non-selective cytotoxicity toward normal cells. Moreover, their therapeutic potential against chronic conditions such as idiopathic pulmonary fibrosis (IPF) remains insufficiently explored. This study aimed to evaluate the efficacy and safety of a natural hydrosol blend, The Greatest Love of Nature (TGLON), in inhibiting cancer cell proliferation and mitigating IPF. Methods: TGLON, composed of 12 steam-distilled plant hydrosols, was chemically characterized by gas chromatography–mass spectrometry (GC-MS). Its cytotoxicity was assessed using the MTT assay against five human cancer cell lines (A-549, HepG2, MCF-7, MKN-45, and MOLT-4) and normal human lung fibroblasts (MRC-5). In vivo safety and therapeutic efficacy were evaluated in Sprague Dawley rats and a bleomycin-induced IPF mouse model, following protocols approved by the Institutional Animal Care and Use Committee (IACUC). Results: TGLON maintained >90% viability in MRC-5 cells at an 80-fold dilution and significantly inhibited the proliferation of A-549 (41%), HepG2 (84%), MCF-7 (50%), MKN-45 (38%), and MOLT-4 (52%) cells. No signs of toxicity were observed in rats administered TGLON orally at 50% (v/v), 10 mL/kg. In mice, TGLON alleviated bleomycin-induced pulmonary inflammation and fibrosis. Conclusions: TGLON exhibited selective anticancer and anti-fibrotic activities under non-toxic conditions, supporting its potential as a bioactive agent for early-stage disease prevention and non-clinical health maintenance.